Dojrzałość informatyczna a ryzyko wdrożeń systemów informatycznych - Jur, Michał (IT maturity and risk of IT implementation projects, 2006)
The article begins with definition of the company’s maturity. Then the author discusses some risk criteria of IT implementation projects. Then the author shows the influence of company IT maturity on risk of IT implementation projects. The conclusion is that immaturity can be the source of IT implementation projects failure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 256-264